Adolescent antisocial behavior under an approach which integrates three criminological theories [Conducta antisocial adolescente bajo un enfoque integrador de tres teorías criminológicas1] (2017)
"In order to contrast the theories of Differential Association, Social Control and General Crime, the relationship between antisocial behavior and the constructs of the theories was analyzed, namely, ""favorable definitions"" (differential association), ""attachment"" ( Social Control) and ""self-control"", using a propositional integrated side-by-side approach of Tibbets and Hemmens, (2010) that allowed to determine the weight of said constructs in the prediction of antisocial behavior through a binary logistic regression model by blocks explanatory variables that included sociodemographic variables such as sex and the size of the city. A total of 2,395 adolescents from schools located in three cities (large, medium and small) of Venezuela were surveyed. It was found that, of the three variables of the differential association theory, the favorable definitions of friends towards participation in criminal acts served as predictors of antisocial behavior at the individual level. Of the ten variables of social control theory, attachment to school and participation in activities without family supervision were predictive. The self-control of the general theory of crime predicts antisocial behavior. It is concluded that the empirical data support the approaches of these theories. © 2017 Universidad del Zulia."